Tyrosine Kinase Gene Polymorphisms in Limousin (Bos taurus) Bull Correlation with Fresh Semen Qualities - Ramadhani, Ageng Ilham; Oktanella, Yudit; Purwatiningsih, Wawid; Hardian, Andreas Bandang; Hernawati, Tatik (Jurnal Veteriner, 2022)
Tyrosine kinase (TEK) is the subgroup of protein kinases class. Tyrosine kinase (TEK) is a protein in spermatozoa plasm that functions as a mediator during spermatozoa penetration to pellucide zone 3 (PZ3) of the ovum. The purpose of this study was to analyse the variation of receptor tyrosine kinase genes related to the fresh semen qualities of limousin bulls, using Polymerase Chain Reaction Restriction Fragment Length Polymorphism (PCR-RFLP) method with HindIII restriction enzyme in A/AGCTT restriction site. This study used 20 blood samples of limousin bull from BBIB Singosari Malang. DNA amplification carried out by PCR method using forward primer (TEK_F) 5'-TAGATTGTCGCTTGCCTGGG-3’ and reverse primer (TEK_R) 5'-CCTGTGCCGACAGGTTTACT-3’. The data analysis were obtained by counting the total of RFLP DNA fragments as the genetic variation. The correlation between the total of RFLP DNA fragments and the fresh semen qualities were analysed by Spearman correlation test with RStudio software. The polymorphic DNA fragments were on 136 bp, 88 bp, 72 bp, and 12 bp range. Monomorphic DNA fragment was on 39 bp range. Correlation coefficient between the RFLP DNA fragments total with semen pH was -0,158 (negative correlation) with the p-value 0,912; semen volume was -0.105 (negative correlation) with the p-value 0,659, sperm motility was -0,050 (positive correlation) with the p-value 0,831; and sperm concentration was 0,044 (positive correlation) with the p-value 0,852. The RFLP DNA fragment total with some fresh semen evaluation parameters had very low correlation with no significancy because of the p-value >0,05.